(untitled) (Indian Journal of Veterinary Pathology, 2025)
Viral pathogens induce distress in poultry and economic loss to farmers worldwide. Infectious Bursal Disease (IBD), a Birna viral immunosuppressive infection of poultry continues to affect birds including regions of Karnataka and neighbouring states; hence study on IBD was undertaken with the objective to estimate its prevalence and understand its pathology. Data from 15 IBD outbreaks from commercial broilers (11) and layers (2) as well as native birds (2) showed average morbidity of 29.3% (7.1 to 100%) and mortality of 18.4% (7.5 to 100%). Maximum number of 9 outbreaks was recorded in the age groups 1-4 weeks accounting for 60 percent of the total outbreaks and the same age group also showed highest morbidity (Average 33.1%, Range: 9-100%) and mortality (Average 22.4%, Range: 7.5-100%). Affected birds showed vascular and atrophic changes in lymphoid organs with secondary changes in liver, kidneys and skeletal muscles. Ultrastructural studies of thymus revealed severe necrosis and increased electron density in lymphocytes and hyperplasia of reticular cells. Bursa also revealed areas of lymphocytic apoptosis and engulfed phagocytic bodies in these macrophages. The cytoplasmic granules of bursal secretory dendritic cell (BSDC) had fused together, forming big, irregularly shaped, electron dense bodies. Amplification of VP2 gene using reverse transcriptase PCR showed 319 bp products having phylogenetic similarity to Indian isolates. Eight IBD outbreaks showed concurrent infection with other pathogens. The bioinformatic analysis of VP-2 protein suggested the presence of the glycine like amino acids predominant in the alpha helical secondary structure.